Optical Reconstruction of High-Speed Surface Dynamics in an Uncontrollable Environment - Luegmair, Georg; Kniesburges, Stefan; Zimmermann, Maik; Sutor, Alexander; Eysholdt, Ulrich; Döllinger, Michael (IEEE Transactions on Medical Imaging, 2010)
The ability to communicate with our voice can be regarded as the concatenation of the two processes "phonation" and "modulation." These take place in the larynx and palatal and oral region, respectively. During phonation the audible primary voice signal is created by mutual reaction of vocal folds with the exhaled air stream of the lungs. The underlying interactions of masses, fluids and acoustics have yet to be identified and understood. One part of the primary signal's acoustical source are vortex induced vibrations, as e. g., created by the Coandaeffect in the air stream. The development of these vorteces is determined by the shape and 3-D movements of the vocal folds in the larynx. Current clinical in vivo research methods for vocal folds do not deliver data of satisfactory quality for fundamental research, e. g., an endoscope is limited to 2-D image information. Based hereupon, a few improved methods have been presented, however delivering only selective 3-D information, either for a single point or a line. This stands in contrast to the 3-D motions of the entire vocal fold surface. More complex imaging methods, such as MRI, do not deliver information in real-time. Thus, it is necessary to develop an easily applicable, more improved examination method, which allows for 3-D data of the vocal folds surfaces to be obtained. We present a method to calibrate a 3-D reconstruction setup including a laser projection system and a high-speed camera. The setup is designed with miniaturization and an in vivo application in mind. The laser projection system generates a divergent grid of 196 laser dots by diffraction gratings. It is calibrated with a planar calibration target through planar homography. In general, the setup allows to reconstruct the topology of a surface at high frame rates (up to 4000 frames per second) and in uncontrollable environments, as e. g., given by the lighting situation (little to no ambient light) and varying texture (e. g., varying grade of reflection) in the human larynx. In particular, this system measures the 3-D vocal fold surface dynamics during phonation. Applied to synthetic data, the calibration is shown to be robust (error approximately 0.5 mu m) regarding noise and systematic errors. Experimental data gained with a linear z-stage proved that the system reconstructs the 3-D coordinates of points with an error at approximately 15 mu m. The method was applied exemplarily to reconstruct porcine and artificial vocal folds' surfaces during phonation. Local differences such as asymmetry between left and right fold dynamics, as well as global parameters, such as opening and closing speed and maximum displacements, were identified and quantified.
Keywords: Biomedical imaging; laser projection system calibration; planar homography; surface reconstruction